THE USE OF PAYUS MEAT (Elops hawaiensis) AS A BASIC MATERIAL IN THE FISH CRACKERS PRODUCTION - Patricia Caroline; Juni Triastuti; Dwitha Nirmala (Universitas Mataram, 2024)
Payus fish (Elops hawaiensis) is a predatory pest in milkfish ponds which has soft-textured flesh with a high enough protein content, namely 22.58%, so it has the potential as a follow-up product such as fish crackers. This research was conducted to determine the optimal amount of carp fish meat in the formulation of good quality and acceptable by the public. This study used a completely randomized design (CRD) with 4 treatments and 5 repetitions. The parameters of this study include swelling power, oil absorption, chemical properties, and organoleptic value of Payus fish crackers. The results showed that Payus fish can be used as a basic ingredient for making fish crackers with the best treatment at P2 which produced 238.81% swelling power, 37.53% oil absorption, 4.29% moisture content, 17.92% protein content, 17.92% protein content. 2.47% fat, and 54.11% carbohydrate content. Has sensory acceptance with an appearance value of 8.40, an odor value of 8.19, a taste value of 7.94, and a texture value of 7.74.